If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 179 + -5x = 6x + 14 Reorder the terms: 179 + -5x = 14 + 6x Solving 179 + -5x = 14 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 179 + -5x + -6x = 14 + 6x + -6x Combine like terms: -5x + -6x = -11x 179 + -11x = 14 + 6x + -6x Combine like terms: 6x + -6x = 0 179 + -11x = 14 + 0 179 + -11x = 14 Add '-179' to each side of the equation. 179 + -179 + -11x = 14 + -179 Combine like terms: 179 + -179 = 0 0 + -11x = 14 + -179 -11x = 14 + -179 Combine like terms: 14 + -179 = -165 -11x = -165 Divide each side by '-11'. x = 15 Simplifying x = 15
| 9(x-3)+8(x+6)=4(8-7x) | | 0.1(x+100)+0.1x=1 | | -1*[-2]=x | | -36-2x+9x=3x+12 | | 5(t-2)-3t=4(2+4)-9 | | 4(2x+9)=20 | | 8a^2+4a= | | 9+n=2n-4 | | 9-10x=94-45x | | (x+2)(2x-3)=0 | | 4x-11x+7=4 | | 5(x+2)+x=3(x-1)+1 | | 24+0.99x=1.49x | | 4(v-3)-6v=-2(v+6) | | 15=-8(c-1)+9 | | x^6-9x^3+20=0 | | 4(v-3)-6v=2(v+6) | | 5(2+y)-y=10+4(y+1) | | 8(2x+3)=56 | | 4x^3+22x^2+52x=0 | | 7(2k-1)+4=7 | | -2(w+4)+6w=4(w-3) | | -x+3=9 | | 5(2x+3)=45 | | -4(v+3)-3v=2(v+3) | | -2(x+4)+6w=4(w-6) | | 12-C+15-C=7 | | 5ax+bx=5abx | | 4(3+x)-x=6+3(x+2) | | 5ax+bx=#5ab2x | | y=56-2 | | 21=9-2(4a+2) |